Development of SMI (Small and Medium Industry) Centres for Fisheries Sector in the Northern Region of Aceh through Community Empowering Around the Coast by Strengthening Networks, Digitization and Downstream Products - Jullimursyida; Sofyan; Deassy Siska; Yesy Afrilia; Cut Hilma Arifa; Saumina; Tursina (LPPM Universitas Malikussaleh, 2022)
Pusong Baro Village and Ulee Jalan Village are two villages located in Banda Sakti district, under the administration of Lhokseumawe City. It has abundant natural wealth from the fishery sector, and has great potential as a dry fish producing village in the Lhokseumawe City area. However, the development of the community's dry fish processing business production is still not good. Problems in the management of dried fish are constrained by the lack of processing of existing dried fish, products that are packaged not yet on standard packaging, marketing of products that are still conventionally so that the sales commodities are small, as well as less qualified marketing management. In overcoming the obstacles of dry fish production in Pusong Baro Village and Ulee Jalan Village, this community service activity provides facilities to the community villages in the form of business tools that facilitate the production process such as vacuum sealer machines, fish drying ovens, oil slicing machines and making fish drying houses . The output of community service activities in Pusong Baro Village and Ulee Jalan Village is that they can develop better dry fish processing, product packaging which has been standardized and interesting, increased ability of community business management, publication of service journals, simple IPR , creation of an introduction catalog website dried fish products as well as uploading videos of service activities on the YouTube platform. With this service activity, it is hoped that production activities can increase to be even better than before and can expand the dried fish market commodity community production of Pusong Baro Village and Ulee Road Village.